Floral ontogeny of Delphinium anthriscifolium (Ranunculaceae) and development of intrafloral and symmetrical resupinated organs. (13th July 2021) - Zhang, Wen-Gen; Liu, Yu-Guang; Nie, Tang-Jie; Guo, Chun-Ce; Qiu, Li-Hong; Yang, Guang-Yao; Jabbour, Florian; Wang, Wei
Abstract: Delphinieae (Ranunculaceae) are characterized by zygomorphic spiral flowers and show a remarkable diversity of perianth organization. Floral structure and development have been investigated in most lineages of the tribe, mainly focusing on the establishment of symmetry and on perianth development. In this study, floral organogenesis and morphogenesis in Delphinium anthriscifolium, a member of the recently erected Delphinium subgenus Anthriscifolium, were investigated and compared with those of other species of Delphinieae in a phylogenetic context. In D. anthriscifolium, zygomorphy of the spiral flower is established soon after the initiation of sepal primordia. Among the four fully developed petals of the dorsoventralized corolla, the two dorsalmost ones become spurred, and the lateral petals resupinate before anthesis and are mirror images of each other. Resupination of petals, long overlooked in morphological studies of Delphinieae, is here reported in Ranunculaceae for the first time. The role of resupinated petals, possibly acting as a landing platform for nectar foragers, may be of high adaptive significance. Based on our new findings regarding floral ontogeny and morphology in D. anthriscifolium, we provide an updated picture of floral evolution in Delphinieae.